1995
DOI: 10.1111/j.1365-2796.1995.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of alcoholism and its relation to cause of hospitalization and long‐term mortality in male somatic inpatients

Abstract: Alcoholism was found in every fourth male somatic inpatient, and an alcohol-related disorder was the cause of hospitalization in one-third of these men. The long-term prognosis did not differ from that in non-alcoholic patients. In the treatment of alcoholics with somatic disorders, it is important to take measures against alcoholism as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…Nielsen et al [7] defined patients with alcohol problems using the MAST and found 28.6% of inpatients having alcohol problems. Other authors screened inpatients of European hospitals with the MAST or the CAGE questionnaire and reported an average figure of 20-25% [5,21,22]. Thus, the present study seems to confirm the high prevalence of patients with alcohol problems found in recent American studies [23,24].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nielsen et al [7] defined patients with alcohol problems using the MAST and found 28.6% of inpatients having alcohol problems. Other authors screened inpatients of European hospitals with the MAST or the CAGE questionnaire and reported an average figure of 20-25% [5,21,22]. Thus, the present study seems to confirm the high prevalence of patients with alcohol problems found in recent American studies [23,24].…”
Section: Discussionsupporting
confidence: 80%
“…Several studies published in the international literature showed between 4 and 70% of the patients considered as alcohol misusers or dependent, but the definition of alcohol misuse varied highly [5][6][7][8]. Previous studies in France have reported prevalence results of alcoholism in populations of general or university hospitals [9][10][11][12] and have found a prevalence of alcohol misusers varying between 13 [11] and 30% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both alcoholism and AD have been associated with institutionalization and mortality (Wallerstedt et al, 1995;Jagger et al, 2000), which could confuse the association between the ALDH2*2 and AD. To clarify this issue, we have subsequently followed our study cohort over a 2.4-year period and further investigated the longitudinal association between the ALDH2*2 allele and incidence of AD.…”
Section: Introductionmentioning
confidence: 96%
“…sample sizes (b500 subjects; Baldwin et al, 1993;Lange & Schacter, 1989;Marik & Mohedin, 1996;Stein, 1994;Wallerstedt, Denison, Sandstrom, & Westin, 1995) and crosssectional data of short duration (from days to months; John, Rumpf, & Hapke, 1999;Lange & Schacter, 1989;Marik & Mohedin, 1996;Orford, Somers, Daniels, & Kirby, 1992;Taylor, Kilbane, Passmore, & Davies, 1986), limited mostly to alcohol consumption and not illicit drug use and usually derived from only one clinical department (medicine or psychiatry).…”
mentioning
confidence: 99%